Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with gastric cancer and peritoneal carcinomatosis. Issue 11 (November 2018) - Rihuete Caro, Cristina; Manzanedo, Israel; Pereira, Fernando; Carrion-Alvarez, Lucía; Serrano, Ángel; Pérez-Viejo, Estíbalitz
Abstract: Background: Gastric Cancer (GC) with Peritoneal Carcinomatosis (PC) has long been regarded as a terminal disease. Over the past two decades, cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) has changed the traditional concept of peritoneal metastases from being a systemic disease, to being considered a locoregional dissemination. Patients and methods: A prospective study was performed at a high-volume Carcinomatosis Center to evaluate survival, morbi-mortality and prognostic factors for survival in a cohort of patients with GC and PC treated with CRS + HIPEC between June 2006 and December 2016. Results: Thirty-five patients were included in the study. Median follow-up was 54 months. Postoperative major complications (>grade IIIa) occurred in 25.7% of patients, including 2 deaths (mortality 5.7%). The median overall survival (OS) was 16 months and the 1-, 3- and 5-year OS rates were 70.8%, 21.3% and 21.3% %, respectively. The median OS for patients with PCI ≤6 was 19 months, in contrast to 12 months for the 19 patients with PCI >6. Three patients were included with only a positive cytology and their median OS was not reached. Perineural invasion was the only factor that had a negative influence in prognosis (HR 18.8) in multivariate analysis. Conclusion: Although GC with PC still has a poor prognosis, survival has improved in selected patients with CRS + HIPEC and perioperative systemic chemotherapy. Patients with isolated positive cytology or peritoneal carcinomatosis with PCI less than 6 had encouraging survival rates.